2007
DOI: 10.1111/j.1472-765x.2006.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel cellulase free alkaliphilic xylanase from alkali tolerant Penicillium citrinum: production, purification and characterization

Abstract: Aims:  The enzymatic hydrolysis of xylan has potential economic and environment‐friendly applications. Therefore, attention is focused here on the discovery of new extremophilic xylanase in order to meet the requirements of industry. Methods and Results:  An extracellular xylanase was purified from the culture filtrate of P. citrinum grown on wheat bran bed in solid substrate fermentation. Single step purification was achieved using hydrophobic interaction chromatography. The purified enzyme showed a single ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 26 publications
3
39
0
6
Order By: Relevance
“…The peaks were used for subsequent characterization and properties of enzymes. These purification techniques are comparable to those reported by [108,109,110,111] using sephadex G-100; sephadex G-150; sephadex G -50 and G -200 and superdex-200 HR respectively. …”
Section: Cellulases Purification and Activitysupporting
confidence: 65%
“…The peaks were used for subsequent characterization and properties of enzymes. These purification techniques are comparable to those reported by [108,109,110,111] using sephadex G-100; sephadex G-150; sephadex G -50 and G -200 and superdex-200 HR respectively. …”
Section: Cellulases Purification and Activitysupporting
confidence: 65%
“…So to obtain high-titre extremophilic cellulase, alkali tolerant Penicillium citrinum MTCC 6489 was isolated from soil. Previous reports showed that P. citrinum MTCC 6489 produce high extent of alkaliphilic xylanase [10,11]. This paper reports for the first time about the production and properties of cellulases from the same P. citrinum.…”
Section: Introductionmentioning
confidence: 79%
“…P. janthinellum produces cellulase at an ideal rate, 28,29) and P. citrinum produces cellulase and xylanase for which neutral pH is optimum. 30,31) P. pinophilum produces 1.9 U/mL of EG in a cellulose-supplemented synthetic culture medium, and P. purpurogenum produces 24 U/mL of EG in a peptone-containing culture medium. 32) The secreted enzyme of the present strain, P. oxalicum A592-4B, is efficient in productivity and produces approximately 5 U/mL of EG in a semi-synthetic culture medium supplemented with rice straw and yeast extract.…”
Section: Discussionmentioning
confidence: 99%